2020
DOI: 10.1002/nau.24554
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐reported outcomes in the setting of a randomized control trial on the efficacy of transcutaneous stimulation of the posterior tibial nerve compared to percutaneous stimulation in idiopathic overactive bladder syndrome

Abstract: Aim: To compare the efficacy of transcutaneous tibial nerve stimulation (TTNS) with percutaneous tibial nerve stimulation (PTNS) regarding patientreported outcomes measures, specifically quality-of-life (QoL) improvement and patient's treatment benefit, on symptoms associated with overactive bladder (OAB). Methods: Patients with refractory OAB symptoms and detrusor overactivity were randomized to receive TTNS or PTNS for 12 weeks. Data from self-report OAB questionnaire short form (q-SF) and incontinence (I)-Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Of the 15 articles remaining, eight were deemed ineligible after full text assessment, leaving seven eligible articles representing six RCTs (Figure 1). 5,14–19 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 15 articles remaining, eight were deemed ineligible after full text assessment, leaving seven eligible articles representing six RCTs (Figure 1). 5,14–19 …”
Section: Resultsmentioning
confidence: 99%
“…The nighttime micturition frequency data was reported by three RCTs 15,18,19 . A total of 56 individuals were allocated to TTNS, and 47 were allocated to control.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…17 In addition, researchers compared the effects of PTNS and TTNS and concluded that TTNS had the same effects as PTNS in relieving patients' relevant symptoms and improving the quality of life. 7,18 It has been recognized that TTNS combined with oxybutynin or low-dose trospium chloride is more effective than a single-drug regimen or TTNS alone. 19,20 Although extensive studies have supported the clinical use of TNS, consensus on the protocol and duration of stimulation treatment has not been reached.…”
Section: Discussionmentioning
confidence: 99%
“…A randomized controlled trial suggested that TTNS not only reduced urgency and nocturia episodes but also improved urodynamic parameters as well as symptom scores and health‐related quality of life scores in the treatment of patients with lower urinary tract symptom (LUTS) 17 . In addition, researchers compared the effects of PTNS and TTNS and concluded that TTNS had the same effects as PTNS in relieving patients' relevant symptoms and improving the quality of life 7,18 . It has been recognized that TTNS combined with oxybutynin or low‐dose trospium chloride is more effective than a single‐drug regimen or TTNS alone 19,20 .…”
Section: Discussionmentioning
confidence: 99%